2008
DOI: 10.1039/b714597g
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of orbital interactions in the additions of phosphonyl and acyl radicals to double bonds

Abstract: Calculation of the barriers for addition of the H2P(=O) and HC(=O) radicals to alkenes, at the CCSD(T)/aug-cc-pVDZ//BHandHLYP/6-311G** level, indicates that both radicals display ambiphilic behaviour. For the HC(=O) radical this behaviour occurs because a secondary orbital interaction of the type pi*(C=O)<--HOMO acts in conjunction with the primary SOMO<--HOMO interaction to balance the SOMO-->LUMO interaction. For the H2P(=O) radical, on the other hand, the much higher-lying LUMO (the sigma*P-O orbital) allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
1
7
1
Order By: Relevance
“…Single-point energy calculations using the BH and HLYP and ROMP2 methods, and B3LYP/6-31G* optimized geometries gave the least accurate energies contrary to that previously reported28 for the prediction of energy barriers in which BHandHLYP provided good agreement with the highest levels of theory used in that study. Moreover, single-point energy calculations at the CCSD(T)/cc-pVDZ, CCSD/aug-cc-pVDZ, QCISD/cc-pVDZ, and QCISD/aug-cc-pVDZ levels of theory with the B3LYP/6-31G* optimized geometries gave 1.2-2.1 kcal/mol energy difference compared to that obtained with CBS-QB3.…”
Section: Benchmark Studiescontrasting
confidence: 99%
“…Single-point energy calculations using the BH and HLYP and ROMP2 methods, and B3LYP/6-31G* optimized geometries gave the least accurate energies contrary to that previously reported28 for the prediction of energy barriers in which BHandHLYP provided good agreement with the highest levels of theory used in that study. Moreover, single-point energy calculations at the CCSD(T)/cc-pVDZ, CCSD/aug-cc-pVDZ, QCISD/cc-pVDZ, and QCISD/aug-cc-pVDZ levels of theory with the B3LYP/6-31G* optimized geometries gave 1.2-2.1 kcal/mol energy difference compared to that obtained with CBS-QB3.…”
Section: Benchmark Studiescontrasting
confidence: 99%
“…Variations in energetics as a function of basis set and method was assessed using B3LYP/6-31G* geometries and single-point energies at B3LYP/6-31+G**, B3LYP/6-311++G**, B3LYP/aug-cc-pVDZ, BHandHLYP/6-31+G**, mpw1pw91/6-31+G** and PBE1PBE/6-31+G** levels of theory. Reaction energy at the B3LYP/6-31+G**//B3LYP/6-31G* is within ∼1 kcal/mol difference of the energetics calculated at the B3LYP/aug-cc-pVDZ and BHandHLYP/6-31+G** levels (see Table S1 of Supporting Information), therefore, B3LYP/6-31+G**//B3LYP/6-31G* offers a reasonable approximation to the higher-level basis set and BHandHLYP/6-31+G** which is effective in approximating barrier height energies (29, 30). Density functional theory (DFT) (31, 32) was applied in this study to determine the optimized geometry, vibrational frequencies, and single-point energy of all stationary points (3336).…”
Section: Methodsmentioning
confidence: 75%
“…The B3LYP/6-31+G(d,p) and ROMP2/6-311G(d,p) levels gave the lowest estimate of the energy barriers while the BHandHLYP/6-311G(d,p)//B3LYP/6-31G(d) and ROMP2/cc-PVDZ//B3LYP/6-31G(d) gave bottom-of-the-well energy barrier estimates that are close to those of the more accurate QCISD/cc-PVDZ//B3LYP/6-31G(d) level. Moreover, a reasonable estimate was also obtained with PCM/BHandHLYP/6-311G(d,p)//BHandHLYP/6-31G(d) and a slighty lower estimate was obtained with the BHandHLYP/6-311G(d,p)/BHandHLYP/6-31G(d) level, which was preferred by Krenske and Schiesser . Therefore, the use of both BHandHLYP/6-311G(d,p)//B3LYP/6-31G(d) and ROMP2/cc-PVDZ//B3LYP/6-31G(d) levels of theory should justify calculation of approximated energetics of decomposition in this study.…”
Section: Resultsmentioning
confidence: 93%
“…It has been shown by Krenske and Schiesser that B3LYP-based approaches using small basis sets (cc-pVDZ or 6-31G(d)) gave lower estimates of the energy barriers for the addition of phosphonyl or acyl radicals to double bonds, and that the BHandHLYP functional provided reasonable estimates to the higher level barriers. They also found that BHandHLYP, using the basis sets cc-pVDZ or 6-311G(d,p), gave similar estimates as the QCISD or CCSD(T) single-point calculations.…”
Section: Resultsmentioning
confidence: 99%